Analisis Gerak Biomekanika (Kinovea Software) Untukmengembangkan Kemampuan Akurasi Shooting Sepakbola Pada Mahasiswa Fakultas Ilmu Ke Olahragawaan Universitas Negeri Makassar - Ilham Kamaruddin; Ambo Dalle; Andi Muh. Raehan; Asdar Musa; Andi Anisa Ade Triyenie (Departement of Mathematics Education, 2024)
Research assesses movement, shooting accuracy and knee angle in football. Using a biomechanics approach with Kinovea’s software, the study aims to evaluate the process of recording such movements, focusing on the advantages and disadvantages of the method. The sample consisted of 30 fourth semester students in the Physical Education, Sports, and Recreation Study Program at (UNM). This study used a survey method with an observational approach to analyze the relationship between knee angle and ball speed in the context of football shooting techniques. Visual recording of shooting motion techniques is done with a camera and analyzed using Kinovea’s software. The research sample consisted of 30 Physical Education, Health, and Recreation (PJKR) students who had the best shooting accuracy and were male at Makassar State University. Data on ball velocity and knee angle were analyzed using the SPSS program version 25. The results showed a Pearson correlation coefficient of 0.591, with a significance (2-tailed) of 0.001, indicating a positive and significant relationship between knee angle and ball speed. However, it should be noted that correlation does not imply causality. The first model has a coefficient of determination (R Square) of 0.349, indicating that about 34.9% of the variability in ball velocity can be explained by knee angle. An Adjusted R Square value of 0.326, indicating that the addition of predictor or sample variables will not provide a significant improvement in explaining ball velocity variability. Although there is a strong and significant relationship between knee angle and ball speed, other factors such as player technique and environmental factors can also influence this relationship. Therefore, more research is needed to understand the additional factors that influence this relationship as well as to establish a causal relationship between the two variables.